Utilizing IFC for shield segment assembly in underground tunneling - Zhou, Y.; Wang, Y.; Ding, L.; Love, Peter (Elsevier BV, 2018)
© 2018 The shield method is a common approach used for subway tunnel excavation. A critical function of the shield method is the segment assembly process. It is, therefore, imperative to have access to information to be able to manage and control the performance of segment assembly during the construction process. However, an issue that hinders the capacity to undertake these tasks during construction is the inability of existing Building Information Modeling (BIM)-related software used to design tunnels to support information exchanges during a project's execution. The Industry Foundation Class (IFC) has evolved as an open and neutral data format to support information exchanges, but they are yet to be able to accommodate the segment assembly process. Considering the absence of such a data format, this research contributes to the extant literature through extending the IFC standard by treating the segment assembly shield used in construction as an ‘object’. It also proposes a new typesetting (i.e. positioning of segments) algorithm that can be used to automatically determine constraints. Moreover, the algorithm can define the design information that is required to enact data exchanges during construction. The newly developed IFC extensions are validated by demonstrating the successful transfer from a tunnel's parametric design models to the segment assembly system.